American index exchange movement against IDX stochastic - Flavianus, Muhammad; Maulani, Alfi (Journal of Natural Sciences and Mathematics Research, 2025)
A giant warehouse full of countless opportunities forms the foundation of this study, which aims to conduct stochastic modeling of the impact of the movement of the American stock index on the IDX (Indonesia Stock Exchange). This research discusses and emphasizes how the movement of the American stock index affects changes in the IDX over a certain period of time using a quantitative approach. The study employs a Hidden Markov Model (HMM) to identify latent market states. It utilizes the Viterbi method to determine the most probable sequence of state transitions based on the observed data. The model was trained using historical movements of the NASDAQ, NYSE, and DOW JONES indices, facilitating the discovery of significant trends in IDX changes. The research results show a trend in the movement of the IDX based on the movement of the American indices NASDAQ, NYSE, and DOW JONES, as follows: Bullish, bearish, bullish, bearish when NASDAQ is observed at 1, 2, 5, 6, and 8; NYSE is observed at 1, 3, 9, 11, and 15; and DOW JONES is observed at 1, 3, 4, 7, 9, 10, 11, 12, 13, 15, and 16. Bearish, bullish, bearish, bullish when NASDAQ is observed at 3, 9, 11, and 15; NYSE is observed at 2, 5, 6, and 8; and DOW JONES is observed at 2, 5, 6, 8, and 14. Bearish, bullish, bearish, bearish when NASDAQ is observed at 4, 12, and 16. Bullish, bearish, bullish, bullish when the NYSE is observed at 4 and 12. Bullish, bearish, bearish, bullish when NASDAQ is observed at seven and when NYSE is observed at 10. Bearish, bullish, bullish, bearish when NASDAQ is observed at 10. Bearish, bearish, bullish, bearish when NASDAQ is observed at 13 and 14. Bullish, bullish, bearish, and bullish when the NYSE is observed at 13, 14, and 16. The analysis indicates that IDX trends generally fluctuate in line with major U.S. indices (NASDAQ, NYSE, DOW JONES). Notably, specific observations 4, 12, 13, 14, 16 reveal a stronger correlation: a bearish NASDAQ movement tends to align with a bearish IDX stochastic, whereas a bearish NYSE movement is more likely to trigger a bullish response in the IDX.